FAKTOR-FAKTOR YANG MEMPENGARUHI BRAND LOYALTY PADA SMARTPHONE REALME DI JAKARTA - Arbi Siti Rabiah; Jeffry Jeffry (Sekolah Tinggi Ilmu Ekonomi Dr Kh Ez Mutaqien, 2022)
This study aims to analyze the factors that influence brand loyalty on Realme smartphone it is perceived quality, brand communication, customer satisfaction, Brand Trust. The data obtained in this study through an online survey using a questionnaire instrument and obtained 100 respondents who use smartphone Realme in Jakarta. Data is processed by Structural Equation Modeling (SEM) with Partial Least Square (PLS) Technique.